2003
DOI: 10.1016/j.chembiol.2003.11.010
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3-Selective Inhibitors Derived from Tyrian Purple Indirubins

Abstract: Gastropod mollusks have been used for over 2500 years to produce the "Tyrian purple" dye made famous by the Phoenicians. This dye is constituted of mixed bromine-substituted indigo and indirubin isomers. Among these, the new natural product 6-bromoindirubin and its synthetic, cell-permeable derivative, 6-bromoindirubin-3'-oxime (BIO), display remarkable selective inhibition of glycogen synthase kinase-3 (GSK-3). Cocrystal structure of GSK-3beta/BIO and CDK5/p25/indirubin-3'-oxime were resolved, providing a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
599
1
19

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 754 publications
(642 citation statements)
references
References 63 publications
(6 reference statements)
23
599
1
19
Order By: Relevance
“…To analyze the role of canonical Wnt signaling in migration of cranial NC cells, 6-bromoindirubin-3'-oxime (BIO), an inhibitor of GSK3ß was used (Meijer et al, 2003;Myers et al, 2014) Similarly to treatments at premigratory stages, the separation of the cranial NC cells into branches in this phenotype was not disrupted, but a reduction of the Twist-expressing cells was again observed. In addition, the embryos treated at migratory stages also showed the 'merged branches'…”
Section: Activation Of Canonical Wnt Signaling By Bio and Treatment Cmentioning
confidence: 99%
“…To analyze the role of canonical Wnt signaling in migration of cranial NC cells, 6-bromoindirubin-3'-oxime (BIO), an inhibitor of GSK3ß was used (Meijer et al, 2003;Myers et al, 2014) Similarly to treatments at premigratory stages, the separation of the cranial NC cells into branches in this phenotype was not disrupted, but a reduction of the Twist-expressing cells was again observed. In addition, the embryos treated at migratory stages also showed the 'merged branches'…”
Section: Activation Of Canonical Wnt Signaling By Bio and Treatment Cmentioning
confidence: 99%
“…In addition, whether the HEK 293-TOP cells specifically responded to canonical Wnt/β-catenin signaling was also examined in this study. Two GSK-3β inhibitors LiCl and BIO, which are able to increase β-catenin stability and induce β-catenin nuclear translocation (26), were used in this study. LiCl competes for the cofactor Mg 2+ and blocks GSK-3β kinase activity, while BIO selectively binds to the ATP binding pocket of the kinase and inhibits enzyme activity (26).…”
Section: Discussionmentioning
confidence: 99%
“…Two GSK-3β inhibitors LiCl and BIO, which are able to increase β-catenin stability and induce β-catenin nuclear translocation (26), were used in this study. LiCl competes for the cofactor Mg 2+ and blocks GSK-3β kinase activity, while BIO selectively binds to the ATP binding pocket of the kinase and inhibits enzyme activity (26). Our results with HEK 293-TOP showed that luciferase activity increased in the presence of BIO or LiCl.…”
Section: Discussionmentioning
confidence: 99%
“…Although not ideal, the ease of knockdown and overexpression in Xenopus often provides a good correlation with specificity. As a result, Xenopus assays are frequently used to validate compounds that affect Wnt and other pathways (Liu et al, 2005;Meijer et al, 2003). The drug-protein interaction will also ideally be rapid and reversible; in some cases, competitive inhibitors can be used to test both speed and reversibility, as with small molecule effectors of Hedgehog signaling (FrankKamenetsky et al, 2002).…”
Section: Forward Screens Using Xenopusmentioning
confidence: 99%